Islam dan Ekonomi Sirkular: Perspektif Ekologi dan Teknologi Hijau di Indonesia - Winata, Nadia (Yayasan Albahriah Jamiah Indonesia, 2025)
Environmental sustainability issues are a global challenge that demands a new, more environmentally friendly economic paradigm, one of which is through the implementation of a circular economy that emphasizes the principles of waste reduction, recycling, and resource reuse. In the Indonesian context, the discourse on the circular economy can be enriched with an Islamic perspective that teaches ecological balance, ethical consumption, and the responsibility of the caliph towards the earth. This study aims to analyze the relationship between Islamic principles, the implementation of the circular economy, and green technology as a sustainability strategy in Indonesia. The research method used is a qualitative descriptive approach with a literature study approach, which examines primary and secondary sources related to Islamic teachings, circular economy practices, and green technology policies in Indonesia. The results show that Islamic teachings through the concepts of isrāf and tabżīr provide a normative basis for suppressing consumptive behavior that produces waste, while the values ​​of shūrā and maslaḥah encourage collective participation in environmental management. The implementation of a circular economy in Indonesia is increasingly relevant with the support of green technologies such as renewable energy, sustainable agricultural innovation, and digital waste management that are in line with the maqāṣid al-Syarīʻah. This study also found that integrating Islam and the circular economy can strengthen government policies through regulations based on religious and ecological values, while simultaneously raising public awareness and actively participating in environmentally friendly practices. In conclusion, a circular economy based on Islamic values ​​and supported by green technology has the potential to be a transformative strategy in addressing ecological challenges and sustainable development in Indonesia.